Systematic Investigation of the Effects of a Novel Protein Hydrolysate on the Growth, Physiological Parameters, Fruit Development and Yield of Grapevine (Vitis Vinifera L., cv Sauvignon Blanc) under Water Stress Conditions - Franco Meggio; Sara Trevisan; Alessandro Manoli; Benedetto Ruperti; Silvia Quaggiotti (Agronomy, 2020)
In the last decade climate change has impacted viticulture and water deficit has become a major concern in fruit production. Many studies have been carried out to determine the grapevine response to environmental changes and to identify key genetic traits to be used in grapevine breeding. However, in order to better manage climate-related risks, novel viticultural practices are urgently needed. A promising solution for a more sustainable model of viticulture involves the use of biostimulants. In this study, the effectiveness of a novel biostimulant (APR®) belonging to the group of protein thermal hydrolysates was tested on grapevine plants subjected to progressive water deficit conditions. Our results showed that this compound applied to roots before imposing water deprivation mitigates the consequences of stress by sustaining the growth of the younger vegetative organs and limiting the extent of cell dehydration; this positive impact on the plant’s physiological state persisted during the recovery phase. Furthermore, at the end of the growing season, plants treated with the biostimulant, both in optimal water conditions and under water stress, exhibited a greater accumulation of biomass in the aerial part (6.8% and 21.3 %, respectively) and a higher berry diameter (3.4 % and 9.5 %, respectively). Additional work through field trials will be necessary to further substantiate these results and to translate this knowledge into specific practices that grape growers can easily adopt.